Pence, Scott County - Shearmire, Brantlee (Kansas State University, The Chapman Center for Rural Studies, 2011)
In northwest Scott County, where wind is plentiful and trees are few and far between, sits the disappearing small town of Pence, Kansas. Platted on October 27, 1886, Pence is located in Beaver Township, which is in the most northwestern corner of Scott County.
Brantlee Shearmire, “Pence, Scott County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/43.
Keywords: Scott County; Scott City; Pence; gold deposits; Beaver Township; Jonah Harris